CHEWING GUM TO HASTEN BOWEL RECOVERY IN CESAREAN SECTION: A RANDOMIZED CONTROL TRIAL - Zainab, Sadia; Akbar, Amina; Mahboob, Saira; Munir, Shazia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the recovery of bowel function by chewing gum in comparison with standard care. Study Design: Randomized control trial (RCT). Place and Duration of Study: Department of Gynecology and Obstetrics, Combined Military Hospital, Okara Cantt for the duration of 6 months from Apr to Sep 2018. Methodology: After the approval of hospital ethics committee, 100 patients undergoing elective cesarean section were divided into two groups (n=50 in each group). Group A were told to chew gum for 1 hour, four hours postoperatively in addition to standard care. Group B were the control group, with no addition of chew gum. The data were analyzed by SPSS version 20. Qualitative data presented as frequency and percentage; chi-square used to calculate significance. Descriptive data were presented as mean ± SD; T-test used to calculate significance. A p-value less than 0.05 was taken as significant. Results: The two groups did not vary in their demographic profile. The mean time for auscultation of bowel sound was 6.5 hours ± 1.03 in group A versus 9.3 hours ± 1.56 in group B; p-value <0.05. The mean time to passage of flatus was 14.28 hours ± 3.05 in group A versus 18.3 hours ± 3.42 in group B; p-value <0.05. Conclusion: Chewing gum postoperatively results in early return of bowel function, as evidenced by earlier return of bowel sounds and passage of flatus. It can be an inexpensive and convenient method for improved patient comfort and outcomes.